The Study of Effect Export Market Orientation and Marketing Mix Adaptation on Export Performance (Case Study: Non-oil Exporter Firms in Tehran) - Rahim Mohtaram; Mehrdad Movasagh (‫مدیریت بازرگانی, 2018)
The current paper examines the impact of export market orientationand marketing mix adaptation on export performance in Tehran's exports companies. The current paper pursues two major goals; first to figure out export market orientation and marketing mix adaptation strategy impact on export performance and second, to study the role of export market orientation in exports due to the contradictory results of previous studies. A sample of 311 export companies was used to test the hypothesis. Data collected was analyzed using Smartpls software and variance-based structural equation model. The results show export companies psychologically adapt their mix marketing plan best to meet the needs of foreign markets in turbulent environments and close competitive markets. Moreover, the results suggest a positive impact of export market orientation and negative impact of Marketing mix adaptation program on export performance. In addition, the export market orientation has dampened the relationship between the two variables, marketing mix adaptation and export performance with a protectionist role in strategic decision-making of export companies.